Increases in endothelial caveolin-1 and cavins correlate with cirrhosis progression. (September 2015) - Yokomori, Hiroaki; Ando, Wataru; Yoshimura, Kazunori; Yamazaki, Hitoshi; Takahashi, Yoshihito; Oda, Masaya
Highlights: In accordance with the progress of cirrhosis, PTRF (polymerase 1 and transcript release factor) and PRKCDBP (protein kinase C, delta-binding protein) reflect proliferative capillary vessels in fibrotic septa. In the control liver tissue, PTRF was scantly localized on liver sinusoidal endothelial cells (LSECs) and serum deprivation protein response (SDPR) was found mainly on non-coated vesicles in LSECs. Aberrant PTRF and SDPR expressions were observed on caveolae-like structures in the process of differentiation of LSECs related to the progression of cirrhosis. Abstract: Background and aims: Caveolin-1 is associated with flat caveolar domains, invaginated smooth plasmalemmal vesicles, and caveolae. Polymerase 1 and transcript release factor (PTRF) (cavin 1) and serum deprivation protein response (SDPR) (cavin 2) are required for the invagination of caveolae, and PRKCDBP (protein kinase C, delta-binding protein; cavin 3) is required for caveolae budding to form caveolar vesicles. To investigate whether cavins are involved in hepatic sinusoidal angiogenesis and remodeling during progression to cirrhosis, normal control liver specimens and early and late cirrhotic liver specimens were studied. Materials and methods: Cavin-1, cavin-2, and cavin-3 proteins and their gene expression were examined using immunohistochemistry (IHC), Western blotting, and laser capture microdissection (LCM)-polymerase chain reaction (PCR) during progression of cirrhosis caused by hepatitis C. According to the perfusion, fixation methods were designed to reevaluate the precise ultrastructural localizations and changes of cavin-1 and cavin-2 expression on liver sinusoidal endothelial cells (LSECs) facing the sinusoidal blood flow. Results: For IHC, cavin-1 and cavin-2 expressions were found to be upregulated in small angiogenic LSECs with collagen deposition in the perisinusoidal space as well as in the vascular endothelial cells of the remarkably proliferated portal venules, hepatic arterioles, and arterial capillaries within the fibrotic septa of late-stage cirrhotic liver. Cavin-3 was mainly localized in large vessels, and it was detected only scantly on the central vein and hepatic sinusoids in the control liver. In late-stage cirrhotic liver, the intensity of cavin-3 was enhanced mainly on proliferative large vessels in regenerated nodules and in the peripheral regions of nodules and fibrous septa. On conducting immunoelectron microscopy, in the control liver tissue, cavin-1 was found to be localized on the caveolae of hepatic arterial and portal venous endothelial cells, but it was scantly localized on hepatic sinusoidal lining cells, and cavin-2 was found mainly on vesicles in LSECs. In the cirrhotic liver tissue, aberrant cavin-1 and cavin-2 expressions were observed on caveolae-like structures in LSECs. Significant overexpressions of cavin-1 at the protein and messenger RNA (mRNA) levels in a cirrhotic liver were demonstrated by Western blotting and LCM-PCR. Conclusions: Cavin-1 and cavin-2 are strongly expressed within caveolae-like structures and associated vesicles within LSECs of the hepatitis C-related cirrhotic liver. Cavin-1 would play a critical role in regulating aspects of caveolin-1 in LSECs. Moreover, these findings suggest a direct association of cavin-1 and cavin-2 with the process of differentiation and transformation of LSECs inducing hepatic sinusoidal capillarization related to the progression of cirrhosis.